Possibilities of prevention of catheter infections - Cieśla, Danuta; Czerniak, Jolanta (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2008)
Intravenous cannulation is one of the most common procedures performed by nurses in hospitals. Unfortunately this procedure is closely linked with intravenous infections. Nowadays there is quite good medical equipment and the quality of this equipment is better than previously. However, equipment for cannulation such as various kinds of catheters still poses a big medical and economic problem because of intravenous infections. Intravenous infections are linked to various factors such as: interaction in the human body with pathogens, presence of venous catheter, and their duration. These factors linking with each other are very dangerous, because of the risk of infections. The main source of infections are: presence of pathogens on the human skin where the catheter is situated, and the hospital environment. That is why we have to prevent intravenous infection, because it is very important and necessary. This article shows risks factors, prevention of intravenous infections and procedures against infections.